Implementasi Perpustakaan Sekolah Sebagai Sumber Belajar Kelastinggi Di SDN Kawatan No 19 Surakarta - giyarti, giyarti, Drs. Suwarno, SH., M. Pd (2017)
This study aims to: 1) Describe the implementation of school libraries as a source of high-class learning at SDN Kawatan No 19 Surakarta. 2) To describe what are the barriers to the implementation of school libraries as a source of high-class learning at SDN Kawatan No 19 Surakarta. 3) Describe how the implementation of library solutions as a source of high-class learning at SDN Kawatan No 19 Surakarta. This type of research uses qualitative research type. Data collection techniques used are observation, interview and documentation. The validity of this research data using source and method triangulation. Data were analyzed interactively. The result of the research shows that 1) Implementation of School Library as a Learning Source of High Class SDN Kawatan No 19 Surakarta. This implementation is seen from the school library construction and the implementation of the school library has not maximized to make the ideal library: a) The construction of school library. (1) Library status is not effective yet (2) Library staff has not done their job well (3) Library collection is enough but old book (4) Insufficient equipment for class 1 high class (5) Space / Library Building is sufficient but less (6) Library budget is not maximized in use to finance various expenses (7) Service or service does not yet have 8) Socialization / Promotion Library using through parents only 9) Improved Reading Interest / Use of Library not yet optimal (10) Cooperation does not have 11 ) Library Partners have been running DINAS, DAK, Boss Funds, Committee (12) The review or evaluation of the library has made regular improvements but not maximal b) the implementation of school libraries (1) given the rest time (2) the assignment of teachers.2) Implementation barriers The school library as a learning resource in SDN Kawatan No 19 Surakarta includes: a) less librarians b) Mint raises A read difficult students c) Implementation of school libraries only: (1) Provision of rest time (2) Assigned teachers 3) Solutions implementation of school libraries as a source of learning in SDN Kawatan No 19 Surakarta include: a) The existence of parental assistance to participate to increase interest Reading in the school library b) Serviceoptimized c) Presence of reference aids d) giving special time Keywords: school library, learning resources